Santhal Spirituality And Religious Traditions: A Study Of Nature Worship And Cultural Identity - Bilal Ahmad Mir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The study examines the religious practices and cultural importance of the Santhal tribe which is a well-known Munda ethnic group in the Indian subcontinent. The Santhals are one of the largest indigenous communities in India with a population of over seven million according to the 2011 Census of India (Census of India, 2011). This study uses a literature review method to investigate the origins of the Santhal tribe and their unique religious rituals which are mainly focused on the worship of nature and sacred groves known as Sarna. By using linguistic studies historical stories and ethnographic research the study explains the details of Santhal spirituality. This includes their beliefs in a supreme God called Marang Buru and a variety of spirits known as bongas. The study also highlights how the Santhal community balances tradition and modernity and shows how their cultural heritage remains strong despite urbanization and outside influences. The detailed examination helps us better understand indigenous religious traditions and shows that Santhal religious identity remains active even as society changes. The findings contribute to the broader literature on indigenous religions and demonstrate how Santhal spirituality maintains its distinctiveness while adapting to contemporary challenges (Troisi, 2000; Carrin & Tambs-Lyche, 2008).